AKTIVITAS KOMUNIKASI PEMASARAN TERPADU DI AKUN FANBASE TWITTER OFFICIAL 7BTS UPDATE SEBAGAI SARANA LOYALITAS TERHADAP BOYBAND BTS - Muthia Syafira Mawardha; Oktaviana Purnamasari (Universitas Muhammadiyah Jakarta, 2022)
AbstractSouth Korean culture that entered Indonesia can be seen by the amount of content on social media. In today's era of globalization, the relevance of a musician is no longer based on traditional media, but new media such as social media also play a very important role in disseminating information. Especially in the aspects of culture, economy, and politics. This expansion of the fan community has also affected the area of fandom activity, particularly through the fanbase account. The case study conducted with internet mediated interviews and online observations aims to understand the activities, involvement and role of a fanbase account in promoting BTS through Integrated Marketing Communication. The results of the study will explain that the communication that occurs within the fandom will have a strong impact with the artist and strengthen the means of loyalty both as fans and as consumers of the company.Keywords: Fans, Social Media, BTS, Loyalty, Marketing Communication, Integrated Marketing Communication